Mandibular osteomyelitis on panoramic radiographs: a case series - Thala, Ifa Ariefah Hs; Wulansari, Dwi Putri; Rasul, Muhammad Irfan (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2025)
Objectives: This series of cases aims to see an extension of a lesion using panoramic radiographs to help establish a diagnosis in three cases in the mandible. Osteomyelitis occurs more often in the mandible than in the maxilla because the maxilla has a better blood supply than the mandible, with relatively thinner cortical and fewer medullary cavities. Case Report: Three female patients presented with nearly identical complaints, including frequent pus discharge, unpleasant odor, and swelling. Only two of the patients had a history of tooth extraction. All three were referred to the university dental hospital (RSGM) for further management. Panoramic radiographs revealed similar findings among the three cases, including mixed radiopaque-radiolucent images with irregular shapes and diffuse borders. In two patients, sequestra were visible in the right and left corpus regions of the mandible. In contrast, the third patient showed a slightly different presentation: a well-defined, irregular radiopaque mass protruding from the top of the alveolar bone, localized at the crest of the ridge. One of the patients had a history of systemic diseases, specifically hypertension which was under control. Conclusion: In these three cases, a panoramic X-ray examination was the only support for identifying the characteristics of lesion expansion and was considered sufficient as a reference for patient management. However, a definitive diagnosis still requires a histopathological examination.